Purpose in Life and Character Strengths as Predictors of Health Sciences Students’ Psychopathology During the COVID-19 Pandemic - Echeverria, Iván; Peraire, Marc; Penadés, Danaide; Quintero, Valentina; Benito, Ana; Almodóvar, Isabel; Haro, Gonzalo (Frontiers in Psychiatry, 2022)
Background: Health sciences students experience high levels of psychopathology conditioned by psychosocial, financial, and academic factors. However, COVID-19 pandemic might even have worsened their mental health. Thus, this article aims to evaluate how the exposure to COVID-19 pandemic has affected these students’ mental health and to determine the effect of purpose in life and character strengths on this psychopathology. Methods: A cross-sectional study of unpaired samples was carried out in Spain during the first and third waves of the pandemic in 70 medical and 52 nursing students. Results: The risk factor that most determined the appearance of anxiety was the exposure of family and friends to COVID-19 (OR= 4.01; p < 0.001), while the most protective factors were honesty (OR= −1.14; p = .025) and purpose in life (OR= −.18; p<.001). Purpose in life also protected against the onset of depression and total psychopathology. In addition, we observed studying medicine was a protective factor against total psychopathology while being a nursing student was associated with high levels of acute stress. Conclusion: Exposure of the students’ family and friends to SARS-CoV-2 favoured the appearance of symptoms of anxiety. Honesty had a preventing role in the onset of anxiety and a high purpose in life was protective against the appearance of anxiety, depression, and total psychopathology.